Morality tales: Young women's narratives on offending, self-worth and desistance. (September 2019) - Larsson, Birgit
This article emerges from a study of female offenders' participation in police-facilitated restorative justice in one county in England. The qualitative study presented here is based on life history interviews with 12 women and focuses on three morality tales that emerged through narrative analysis: 'offending as play', 'the strong woman' and 'work and a normal life'. The women used these tales to protect self-worth and justify 'bad' behaviour in order to counter professional responses which they viewed as stigmatising. The paper concludes with implications for practice with girls and women who offend, which may benefit police, probation and social workers.